Calcium Chloride and Salinity Stress Effects on Growth, Dry Matter Allocation and Ion Uptake of Sweet Potato (Ipomoea batatas [L.] Lam.) - Richardson, Kenneth Vincent Austin; PDS, Caligari (JOURNAL OF ROOT CROPS, 2015)
The effects of NaCl salinity and CaCl2 concentrations on growth, dry matter allocation and ion uptake of sweet potato (Ipomoea batatas [L.] Lam.) plants were examined. Responses of sweet potato to salinity showed that plants growing in low Ca2+ exhibited severe growth reduction under salinity stress of 140 mM NaCl. Growth was reduced by NaCl salinity, and differences in ion uptake were observed between the plants receiving low and high concentrations of CaCl2. Relative growth rate (RGR) of sweet potato was only slightly reduced by salinity in the early stages, with a large reduction occurring in the later stages. Sweet potato had a higher dry matter allocation to its shoots as NaCl salinity reduced root growth more than it did shoot growth. Salinity tolerance of sweet potato appears to be associated with its ability to control rates of Na+, K+ and Ca2+ ion uptake and transport, in order to maintain ionic adjustments within the plant tissues during salt stress. There appears to be a salt tolerance mechanism operating in which, during salt stress, ionic adjustment within the plant tissues of sweet potato cultivar is maintained by controlling the rates of ion uptake and transport.